Kinerja Kebijakan Fiskal Daerah di Indonesia Pasca Krisis - Asnita Frida Sebayang (Economic Journal of Emerging Markets, 2005)
In 1999-2002, most of regions have a specific pattern in efficiency. This de¬pends on characteristics of the regions. The greatest different among of regions is fiscal ca¬pacity. Using Data Envelopment Analysis, performance of fiscal policy can be measured. Some variables that used are General Transfer (DAU), Routine Expenditure, Expenditure for Transportation, Local Tax, and Local User Charge.This study found, there are two regions that achieve best performance. They are DKI Jakarta and East Java. These regions are not only efficient but also consistent. Most of effi¬cient region will be a benchmark to the others. On the other hand, each region that is inefficient has different source of inefficiency. Some of them are inefficient in DAU, expenditure, local tax and user charge.The pattern of fiscal capacity and fiscal policy performance indicate that there is a regional development gap in Indonesia. Bali and Java have better performance relative to the others. Because of specific characteristic of region, it is important to make a specific ap¬proach for each region. Keywords: Fiscal Capacity, Fiscal Policy Performance, DEA.